Rancang Bangun Aplikasi Diskusi Mahasiswa Sebagai Sarana Kolaborasi Di Universitas Katolik Santo Thomas - Tumanggor, Ferdinan; Sitorus, Lamhot (KAKIFIKOM : Kumpulan Artikel Karya Ilmiah Fakultas Ilmu Komputer, 2025)
Catholic University of Santo Thomas is committed to providing high-quality education by emphasizing moral and ethical values, as well as students' academic abilities. In the era of rapid information and communication technology, the need for an effective means of collaboration is increasingly urgent, especially to address the issue of spreading gossip and bad information on campus. Gossip and negative news can damage a university's reputation, cause conflict, and disrupt the learning process. To overcome this, a solution is needed that can facilitate productive discussions and maintain content security in the campus environment. This research aims to develop a web-based student discussion application that prioritizes security and convenience. This application is designed for collaboration with discussions that are free from negative content with technologies such as Google Vision API and Perspective API, and supports collaboration through advanced features such as Gemini AI to find automatic conclusions.